High CO Adsorption Performance of CuCl-Modified Diatomites by Using the Novel Method “Atomic Implantation” - Manh B. Nguyen; Tuyen V. Nguyen; Giang H. Le; Trang T. T. Pham; Khu Le Van; Giang T.T. Pham; Tung Ngoc Nguyen; Quang Vinh Tran; Tuan A. Vu (Journal of Chemistry)
An atomic implantation method was used to modify diatomite with CuCl. The CuCl/diatomite samples were characterized by different techniques, including FTIR, XRD, BET, SEM-TEM, EDX, and CO-TPR. Characterization results revealed the formation of CuCl particles of 50–60 nm highly dispersed on diatomite surface. CO adsorption measurements showed that 2CuCl/diatomite exhibits the highest CO adsorption capacity among all CuCl-modified samples with diatomite. Its CO adsorption capacity of 2.96 mmol/g at 30°C is 10 times higher than that of unmodified diatomite (0.29 mmol/g). The CO adsorption on CuCl-modified diatomites was found to fit well with the Langmuir–Freundlich model.